New constraints on varying alpha - Rocha, G; Trotta, R; Martins, C; Melchiorri, A; Avelino, P; Viana, P (2003)
We present a summary of recent constraints on the value of the fine-structure constant at the epoch of decoupling from the recent observations made by the Wilkinson microwave anisotropy probe (WMAP) satellite. Within the set of models considered, a variation of the value of alpha at decoupling with respect to the present-day value is now bounded to be smaller than 2% (6%) at 95% confidence level. We point out that the existence of an early reionization epoch as suggested by the above measurements will, when more accurate cosmic microwave background polarization data are available, lead to considerably tighter constraints. We find that the tightest possible constraint on alpha is about 0.1% using CMB data alone-tighter constraints will require further (non-CMB) priors. (C) 2003 Elsevier B.V. All rights reserved.